2023
DOI: 10.3390/medicina59020195
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of the Possible Contribution of Group Practice of the Transcendental Meditation and TM-Sidhi Program to Reduction in Drug-Related Mortality

Abstract: Background and Objectives: CDC data indicate that the U.S. is experiencing a sustained epidemic of drug-related mortality, with such deaths exceeding a record 100,000 in 2021, up 47% from 2019. Opioids, especially the synthetic opioid fentanyl, account for approximately 75% of this mortality. This study evaluates a proposed Consciousness-Based® approach that may possibly help reduce trends in drug-related fatalities by mitigating what WHO refers to as an “epidemic of stress” in society that helps fuel drug mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…He suggests that understanding this relationship may help explain the observed effects of consciousness technologies, particularly the TM technique on individual health as well as field effects of consciousness on public health. [ 74 ]…”
Section: A Systems Medicine Model For Burnout Stress Cardiovascular D...mentioning
confidence: 99%
See 1 more Smart Citation
“…He suggests that understanding this relationship may help explain the observed effects of consciousness technologies, particularly the TM technique on individual health as well as field effects of consciousness on public health. [ 74 ]…”
Section: A Systems Medicine Model For Burnout Stress Cardiovascular D...mentioning
confidence: 99%
“…Fourth, at the environmental level, empirical research suggests that group practice of the TM program is associated with improving quality of life in communities. [ 74 ] This may be due to the practice’s ability to reduce socio-environmental stress and promote social coherence, thus improving public health.…”
Section: A Systems Medicine Model For Burnout Stress Cardiovascular D...mentioning
confidence: 99%
“…In addition to a range of physical and mental health benefits for adults, research has shown that such practice increases emotional intelligence in 12-14 year-old school children after one year (Rosaen & Benn, 2006), curtails anxiety and stress, leading to reduced symptoms of attention deficit hyperactivity disorder (ADHD) in 11-14 year-old school children (Grosswald et al, 2008), reduces the number of headaches, and the symptoms of depression and anxiety in children and adolescents between the ages of nine and 18 years (Jong et al, 2019), and increases well-being-measured by elevated happiness, resilience, and self-confidence-in 14 year-old school children (Wendt et al, 2015). Dillbeck et al (2020) have elaborated on these and other findings. Of most importance for the present study are findings associated with increased brainwave coherence (Hebert et al, 2005;Travis & Arenander, 2006;Travis et al, 2010), beginning with the pioneering work on electroencephalographic (EEG) brainwave coherence by Banquet and his colleagues (e.g., 1973Banquet and his colleagues (e.g., , 1974Banquet and his colleagues (e.g., , 1980, and subsequent research which shows the coherence experienced by one individual can also be measured in other, unrelated and at-a-distance, individuals (Travis & Orme-Johnson, 1989).…”
Section: Creating Coherence In Collective Consciousnessmentioning
confidence: 99%
“…In the first, studies have addressed the question of what happens within the practice to distinguish it from eyes closed rest and from other mental practices [see e.g., ( Wallace, 1970 ; Jevning et al, 1978 ; Travis and Pearson, 2000 ; Travis and Shear, 2010 ; Mahone et al, 2018 )]. In the second, a larger number of studies have reported associations between the twice-daily practice of TM and benefits for individual and collective health [see e.g., ( Schneider et al, 2012 ; Paul-Labrador et al, 2006 ; Orme-Johnson, 1987 ; Dillbeck and Cavanaugh, 2023 )]. The current secondary analysis of data from a previous report ( Wenuganen et al, 2021 ) concerns a less-pursued but important topic in research, namely, the search for biological mechanisms capable of supporting the reported health and wellbeing benefits of the practice.…”
Section: Introductionmentioning
confidence: 99%